Community engagement in digital banking: Insights from Jakarta and Perth - Husada, Safaruddin; Yunus, Ulani; Ramonita, Latifa; McMahon, Mark (Universitas Padjadjaran, 2025)
Background: In the digital era, community engagement plays a pivotal role in driving market share expansion in the banking sector, yet the impact of such initiatives across diverse regulatory and cultural contexts remains underexplored. Purpose: This study examines the influence of community engagement on the digital bank market share in Jakarta, Indonesia, and Perth, Australia, while addressing disparities in digital access and customer experience. Methods: Employing a quantitative methodology, the study analyzed structured surveys from 300 respondents (150 each from Jakarta and Perth) to uncover relationships between community engagement and market expansion. Results: Findings reveal that robust community engagement significantly enhances customer loyalty and market share in Jakarta, with digital literacy and infrastructure playing a critical role. In Perth, the effect is moderated by regulatory environments emphasizing innovation and consumer trust. These outcomes are inferred through improvements in technical capability, information/media literacy, and user experience, which serve as foundational mediators fostering customer trust, loyalty, and ultimately market expansion. Conclusion: Community engagement is a vital strategy for expanding digital banking market share, yet its effectiveness is contingent on contextual factors such as digital literacy, regulatory frameworks, and customer preferences. Implications: Practically, banks should tailor engagement strategies to local needs, focusing on building trust and addressing digital divides. Theoretically, this research extends the application of Digital Divide Theory in understanding digital banking adoption across contrasting contexts.